Nurses’ Resilience During Covid-19 Pandemic: A Scoping Review - Astuti, Hery Yuliani; Ismail, Suhartini; Johan, Andrew (Alta Dharma Publisher, 2022)
Introduction: During the COVID-19 pandemic, nurses should have resilience or durability can respond to complex and depressing situations. Objectives: To sum up nurses’ resilience during COVID-19. Methods: This article was written by applying scoping review method. Articles were accessed from science direct, Clinical Key, JStore, EBSCO, and Springer Link databases from March to October 2020. The keywords used were Resilience AND Nurse AND COVID-19 Pandemic. Finding: There were some findings related to nurses’ resilience, such as 1) negative resilience, 2) nurses’ resilience signs and symptoms such as anxiety, stress, and depression 3) contributing factors such as education, mental health training, adequate knowledge source, confidence in work accomplishment, active and passive coping. Conclusion: Most nurses experience negative resilience with signs and symptoms that lead to stress, depression, anxiety, and fear of some situations, such as the limited personal precaution equipment, the risk of being infected, and the fear of spreading the virus to family and colleagues. Recommendation: Nurses must immediately come up from stress to perform better healthcare for the patients by implementing strategies such as asking for social support from the closest people for further study.